Quantum control of tunable-coupling transmons using dynamical invariants of motion. (7th March 2023) - Espinós, H; Panadero, I; García-Ripoll, J J; Torrontegui, E
Abstract: We analyze the implementation of a fast nonadiabatic CZ gate between two transmon qubits with tunable coupling. The gate control method is based on a theory of dynamical invariants which leads to reduced leakage and robustness against decoherence. The gate is based on a description of the resonance between the | 11 ⟩ and | 20 ⟩ using an effective Hamiltonian with the six lowest energy states. A modification of the protocol allows us to take into account the higher-order perturbative corrections of this effective model. This enables a gate fidelity several orders of magnitude higher than other quasiadiabatic protocols, with gate times that approach the theoretical limit.